2016
DOI: 10.1088/0031-8949/91/6/065202
|View full text |Cite
|
Sign up to set email alerts
|

Stability and periodicity of high-order Lorenz–Stenflo equations

Abstract: In this paper, we derive high-order Lorenz-Stenflo equations with 6 variables and investigate periodic behaviors as well as stability of the equations. The stability of the high-order Lorenz-Stenflo equations is investigated by the linear stability analysis for various parameters. A periodicity diagram is also computed and it shows that the high-order Lorenz-Stenflo equations exhibit very different behaviors from the original Lorenz-Stenflo equations for both periodic and chaotic solutions. For example, period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Peak numbers are plotted on (σ, r) parameter planes by considering all possible integer pairs within the parameter domains. In each diagram, the numerically computed peak numbers are assigned different colors following the color scheme similar to that of Park et al [2015] and Park et al [2016a].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peak numbers are plotted on (σ, r) parameter planes by considering all possible integer pairs within the parameter domains. In each diagram, the numerically computed peak numbers are assigned different colors following the color scheme similar to that of Park et al [2015] and Park et al [2016a].…”
Section: Methodsmentioning
confidence: 99%
“…Rech [2016] used the Lyapunov exponent for this purpose regarding a related system called Lorenz-Stenflo equations. We instead adopt periodicity diagrams following Dullin and Schmidt [2007], Park et al [2015] and Park et al [2016b].…”
Section: Introductionmentioning
confidence: 99%
“…The latter appear due to various meteorological conditions including different pressure and density gradients, as well as the presence of shear flows [5]. It has been shown that the nonlinear acoustic-gravity waves can appear in the forms of localized solitary vortices [1,5], ordered structures [8], as well as chaos [9] and turbulence [10].…”
Section: Introductionmentioning
confidence: 99%
“…Within the chaotic regimes presented on bifurcation diagrams, one can recognize periodic windows, as regions, in which much more ordered behavior is observed, including strictly periodic variation. In contrast to the chaotic solution, a periodic time series exhibits a repeating pattern of peaks and troughs, thus the number of local maxima of the variable X (X max ) considered here is limited and allows to define the periodicity [Dullin et al, 2007;Park et al, 2016;Moon et al, 2017]. We observe this situation, for example, for r ≈ 81 [ Fig.…”
Section: -6mentioning
confidence: 94%